Control of Logophoric Pronouns in Gengbe - Grano, Thomas; Lotven, Samson (My University, 2019)
Control is a phenomenon in which the subject of an embedded clause (the “controlled argument”) is obligatorily bound by an argument of the immediately embedding predicate (the “controller”). Cross-linguistic research has revealed variation in how control sentences are syntactically instantiated, though no studies to date have documented cases where the controlled argument is realized by an overt logophoric pronoun. Based on novel field data, we argue that precisely this happens in Gengbe (Gbe, Niger-Congo), though only with some embedding verbs (such as dʒí ‘want’) and only when the embedded clause has potential (as opposed to jussive) mood marking. We propose an account of the facts whereby control complements are property-denoting and whereby logophoricity and jussive mood are two independent routes for creating property-denoting clauses. The upshot is a view of control as an emergent phenomenon; there is no “control construction” or “control pronoun” (pro) but rather several independent components of the grammar that interact to give rise to control under certain conditions for principled type-theoretic reasons.
Keywords: Gengbe; logophoric pronouns; embedded clause